2016
DOI: 10.1088/1367-2630/18/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

Pinning and movement of individual nanoscale magnetic skyrmions via defects

Abstract: An understanding of the pinning of magnetic skyrmions to defects is crucial for the development of future spintronic applications. While pinning is desirable for a precise positioning of magnetic skyrmions it is detrimental when they are to be moved through a material. We use scanning tunneling microscopy (STM) to study the interaction between atomic scale defects and magnetic skyrmions that are only a few nanometers in diameter. The studied pinning centers range from single atom inlayer defects and adatoms to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 19 publications
(42 reference statements)
9
96
1
1
Order By: Relevance
“…After overcoming a small energy barrier, a lower energy minimum is obtained corresponding to a stable state where the defect is near the border of the skyrmion, where the magnetic moments have a large in-plane component. This is in agreement with experimental observations [15]. The saddle point on the energy surface between these two states determines the activation energy for pinning and dissociation of the skyrmion from the defect.…”
Section: Skyrmion At a Nonmagnetic Impuritysupporting
confidence: 91%
See 1 more Smart Citation
“…After overcoming a small energy barrier, a lower energy minimum is obtained corresponding to a stable state where the defect is near the border of the skyrmion, where the magnetic moments have a large in-plane component. This is in agreement with experimental observations [15]. The saddle point on the energy surface between these two states determines the activation energy for pinning and dissociation of the skyrmion from the defect.…”
Section: Skyrmion At a Nonmagnetic Impuritysupporting
confidence: 91%
“…Experiments have indicated that atomic defects can act as nucleation and pinning sites for skyrmions [13]. There is a repulsive interaction with non-magnetic defects but if this energy is overcome the skyrmion tends to be pinned by such defects [15,16]. It is important to characterize the energy surface for a skyrmion near an impurity, and assess the activation energy for the attachement and dissociation as well as the effect of the impurity on the lifetime of the skyrmion.…”
Section: Skyrmion At a Nonmagnetic Impuritymentioning
confidence: 99%
“…Finally, we would like to point out that the trapping of magnetic skyrmions has attracted much attention recently. Different techniques have been proposed, for example, using a hole (defect effect) [42,46,47] or electric field gradient [30] to guide the skyrmion motion. Here we would like to point out that a radially gradient magnetic field may be generated by different experimental techniques, such as a magnetic tip or a magnetic dot deposited on top of a thin film.…”
Section: Trapping Multiple Skyrmionsmentioning
confidence: 99%
“…Such obstacles can, however, hinder the motion of the skyrmions towards read or write elements. Due to the complex pulsed motion of the skyrmions, disorder effects may also become more important [32,33].…”
Section: Introductionmentioning
confidence: 99%